PRESERVATION OF GARUT RAMS SPERMATOZOON AS A SOURCE OF MALE GERM PLASM - ARIEF BOEDIONO; HERDIS; MUHAMMAD RIZAL' (SEAMEO BIOTROP, 2004)
This study was conducted to examine the quality of ejaculated sperm by Garut rams to be used for artificial insemination (AI) and viability of sperm that were collected from preserved cauda epididymis (4°C up to 12 days) for assisted reproductive technology. The semen was collected by artificial vagina, with the sperm motility, live sperm, acrosomal intact, and intact plasma membrane observed. Sperm motility was 75%, while for the live sperm, intact plasma membrane and sperm abnormality were 91.5%, 90.0%, and 1.8%, respectively. In the other study, sperm was collected from cauda epididymis by aspiration method and diluted in different media: 1) Brackett Oliphant (BO) media and 2) modified Phosphate Buffer Saline (mPBS). Evaluation of sperm motility and intact plasma membrane were conducted after washing, counting and dilution of the sperm. The results of this study showed that the sperm motility and intact plasma membrane could be maintained better in BO rather than PBS medium although they were not statistically different (P>0.05). At day 12 of preservation, the motility and intact plasma membrane of sperm collected from cauda epididymis were 0.7% and 1.33% for motility and plasma membrane intact, respectively. These findings showed that the Garut rams semen was qualified for AI and frozen processing; in vitro embryo production by introducing the assisted reproductive technology such as intracytoplasmic sperm injection (ICSI) could be applied by using the sperm collected from preserved cauda epididymis until 12 days of preservation at 4°C. Keywords : Reproduction/spcrmatogenesis/inscmination/Garut rams/small ruminant